2015
DOI: 10.1111/phen.12086
|View full text |Cite
|
Sign up to set email alerts
|

Environmental conditions terminate reproductive diapause and influence pheromone perception in the long‐lived moth Caloptilia fraxinella

Abstract: Reproductive diapause enables long‐lived insects to time mating with environmental conditions suitable for offspring development. Plasticity in the perception of pheromones used in sexual communication may enable mate‐finding at the appropriate time of year. The moth Caloptilia fraxinella (Ely) (Lepidoptera: Gracillariidae) undergoes a 9‐month reproductive diapause, during which the male response to pheromone is plastic and is highest during the period of reproductive activity. The mechanisms controlling this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 52 publications
0
10
2
Order By: Relevance
“…In the summer, treatment with octopamine or serotonin lowered EAG response compared to non-treated males, but not compared to those treated with the solvent control, whether the BA was applied alone or in combination with methoprene. Evenden, 2009Evenden, , 2015; however, in the current study, acetone treatment significantly lowered EAG response to pheromone compared to males that were not treated in the summer, and increased EAG response in the fall in Experiment 2. Organic solvents applied topically to insects can disrupt or partially destroy the cuticular wax layer, and can disrupt cell membranes inside the insect (Denlinger et al, 1980), which can subsequently impact insect physiology and behaviour.…”
Section: Discussioncontrasting
confidence: 72%
See 2 more Smart Citations
“…In the summer, treatment with octopamine or serotonin lowered EAG response compared to non-treated males, but not compared to those treated with the solvent control, whether the BA was applied alone or in combination with methoprene. Evenden, 2009Evenden, , 2015; however, in the current study, acetone treatment significantly lowered EAG response to pheromone compared to males that were not treated in the summer, and increased EAG response in the fall in Experiment 2. Organic solvents applied topically to insects can disrupt or partially destroy the cuticular wax layer, and can disrupt cell membranes inside the insect (Denlinger et al, 1980), which can subsequently impact insect physiology and behaviour.…”
Section: Discussioncontrasting
confidence: 72%
“…The environmental cues that males receive when held outdoors prepare them for overwintering, and male C. frax-inella held outdoors express lower pheromone orientation in a wind tunnel than males held indoors under long day, warm conditions (Lemmen & Evenden, 2015). The environmental cues that males receive when held outdoors prepare them for overwintering, and male C. frax-inella held outdoors express lower pheromone orientation in a wind tunnel than males held indoors under long day, warm conditions (Lemmen & Evenden, 2015).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, male moths C. fraxinella reared under increased temperature during their reproductive diapause and subsequently exposed to female sex pheromones in a wind tunnel show more pronounced sexual responses [39]. At higher temperatures, male moths also show a lower level of specificity towards their sex pheromones, due to shifts in behavioural thresholds related to plume orientation and to the elicitation of upwind flight [51].…”
Section: Behavioural Responsementioning
confidence: 99%
“…Very few data are available on how environmental changes will impact pheromone perception, but one recent study showed that the sex pheromone perception was altered in male moth Caloptilia fraxinella under elevated temperature [39].…”
Section: Perceptionmentioning
confidence: 99%